Digital Intelligence Empowers International Chinese Language Teachers’ Development: Construction of Competence Improvement Framework and Resource Platform - Xu, Zhouling; Han, Xiaoni; Xu, Lan; Yuan, Jingyi; Yuan, Yuan (Journal of Advanced Research in Education, 2025)
In the post-pandemic era, the digital transformation of international Chinese language education is urgent, and teachers face issues such as uneven competence in applying digital intelligence technology and mismatched resources. This study surveyed 370 international Chinese language teachers and found that while their use of digital resources has become routine, it lacks depth. To address this, the study, combining the Standards for Professional Competence of International Chinese Language Teachers and the TPACK theory, constructs a “three-stage and nine-dimensional” competence improvement framework and designs an integrated international Chinese language digital resource platform with four modules—resource supply, training, interaction, and feedback—providing support for teachers’ digital intelligence-driven development and the high-quality development of Chinese language education.